Cadmium (Cd) exposure among waste collector in urban area, Malaysia - Syed Ismail, Sharifah Norkhadijah; Salleh, Faridatul Hanim; Zainal Abidin, Emilia; Kather Mahiddin, Nur Azlin; Rangga, Josfirin Uding (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Introduction: Cadmium (Cd) in urine and inhaled dust of the municipal waste operators was assessed. Methods: Urine spot samples were collected and analysed for Cd and creatinine of 60 municipal waste operators between April to June 2013. Respirable dust was collected using personal air sampling pump GilAir-3 and GilAir-5 for 8 working hours. Cd in urine and dust were analysed using the Flame Atomic Absorption Spectrometer (Perkin Elmer A Analyst 800) while urinary creatinine was measured using Reflotron® Plus creatinine. Results: The mean and standard deviation (SD) of Cd in the respirable dust (0.59 ± 50.27 μg/m3) was within the permissible exposure limit (PEL). The level of Cd in urine (0.015 ± 0.0097 μg/g Cr) was lower than the safe limit of 5 μg/g. The creatinine level (173.59 ± 50.27 mg/dl) was within the normal range (20 to 350 mg/dl). The multiple regression model shows smoking and years of smoking were the significant predictors for the Cd in the urine (R² = 0.216 F(3,56) = 5.150, p < 0.05). Conclusion: Municipal waste operators were exposed to minimal Cd exposure while handling waste and the accumulation of this metal urine was correlated with smoking habit.